Pathogenicity and Long-Term Outcomes of Liddle Syndrome Caused by a Nonsense Mutation of SCNN1G in a Chinese Family - Zhang, Di; Qu, Yi; Dong, Xue-Qi; Lu, Yi-Ting; Yang, Kun-Qi; Liu, Xin-Chang; Fan, Peng; Hu, Yu-Xiao; Yang, Chun-Xue; Gao, Ling-Gen; Liu, Ya-Xin; Zhou, Xian-Liang (Frontiers in Pediatrics, 2022)
Objective Liddle syndrome (LS) is a monogenic hypertension consistent with autosomal dominant inheritance, often with early onset high blood pressure in childhood or adolescence. This study aimed to identify the pathogenicity of a nonsense mutation in SCNN1G in a Chinese family with LS and the long-term outcomes of tailored treatment with amiloride. Methods To explore the pathogenicity of candidate variant reported in 2015 by our team, we constructed mutant and wild-type models in vitro and measured amiloride-sensitive current in Chinese Hamster Ovary (CHO) cells using patch clamp technique. Participants were followed up for 7 years after tailored treatment with amiloride. Results A nonsense variant was detected in six members, two of whom were pediatric patients. This mutation resulted in a termination codon at codon 572, truncating the Pro-Pro-Pro-X-Tyr motif. The mutant epithelial sodium channels displayed higher amiloride-sensitive currents than the wild-type channels (P < 0.05). Tailored treatment with amiloride achieved ideal blood pressure control in all patients with normal cardiorenal function, and no adverse events occurred during follow-up. Conclusion We found the pathogenicity of a nonsense SCNN1G mutation (p.Glu571*) with enhanced amiloride-sensitive currents in a LS family with young patients. Tailored treatment with amiloride may be an effective strategy for the long-term control of blood pressure and protection from target organ damage or cardiovascular events, including children and youth patients with LS.